48‐1: Invited Paper: Next Generation Highly Efficient and Stable Phosphorescent Emitting Materials For OLEDs. Issue 1 (25th September 2020) - Choi, Byoung Ki; Cho, Yong Suk; Choi, Jong Won; Kwak, Seung Yeon; Aratani, Sukekazu; Sim, Myung Sun; Koo, Hyun; Kravchuk, Dmitry; Im, Kyu Hyun; Lee, Ji Youn; Kim, So Yeon; Lee, Bang Lin; et al.
Abstract : The efficiency of light emitting materials (dopants) is invariably compromised on moving to the red region of the spectra due to the increase of non‐radiative decay. In order to solve the above problem, we designed a new dopant, and realized organic light emitting diodes (OLEDs) with excellent performance. We achieved extremely high quantum yield of red dopant, fabricated a device with 33% higher efficiency, and improved roll‐off compared to a device with a current state‐of‐the art emitter.